2016
DOI: 10.1177/0954405416673102
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis for frequency domain error of ultra-precision spindle in a flycutting machine tool

Abstract: The ultra-precision spindle is the key component of ultra-precision machine tool, which largely influences the machining accuracy. Its frequency characteristics mainly affect the frequency domain error of the machined surface. In this article, the error measurement setup for the ultra-precision aerostatic spindle in a flycutting machine tool is established. The dynamic and multi-direction errors of the spindle are real-time measured under different rotation speeds. Then, frequency domain analysis is carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…11 Geometry of the spindle shaft The axial bearings adopt the annular porous air supply, and the structure performances meet the following requirements, which are calculated as Eqs.(4-6). (6) Where r1 represents the inner radius, r2 represents the outer radius, Wt represents the bearing capacity, Kt represents the stiffness, Kα represents the angular rigidity, h0 represents the bearing air gap size, and Ct represents the load capacity coefficient, respectively. After above calculations, in order to ensure the spindle system has sufficient strengths, the main dimensions of the spindle shaft are shown in Table 2.…”
Section: Spindle Shaft Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…11 Geometry of the spindle shaft The axial bearings adopt the annular porous air supply, and the structure performances meet the following requirements, which are calculated as Eqs.(4-6). (6) Where r1 represents the inner radius, r2 represents the outer radius, Wt represents the bearing capacity, Kt represents the stiffness, Kα represents the angular rigidity, h0 represents the bearing air gap size, and Ct represents the load capacity coefficient, respectively. After above calculations, in order to ensure the spindle system has sufficient strengths, the main dimensions of the spindle shaft are shown in Table 2.…”
Section: Spindle Shaft Geometrymentioning
confidence: 99%
“…Accordingly, to maintain the processing stability and reduce external interference on ABS, the electromechanical coupling design should be considered. At present, many scholars have considered dynamic characteristics, 5,6 thermal characteristics, 7 and static pressure characteristics 8,9 during designing spindle systems, but rarely considered the integrated design for ABS. With the In this paper, a new design approach for Aerostatic Bearing Spindles (ABS) is firstly proposed which takes into account of the interactions between the mechanical and the servo subsystems, including the integration of electromagnetic effects, static pressure characteristics, servo control and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous spindle error analysis [25], the main spindle errors contain the synchronous errors with the frequency values less than three-fold frequency and with the frequency value of 12-fold frequency and 24-fold frequency, and a low frequency asynchronous error with 0.6 Hz induced by the air film vibration (the frequency value may has small change due to the change of air film status in different periods, but it does not have any influence on the analysis in this paper). When the spindle rotation speed is 390 r/min, the time domain frequencies of the main synchronous errors are 6.5 Hz, 13 Hz, 77.5 Hz and 154.9 Hz.…”
Section: Frequency Domain Error Allocationmentioning
confidence: 99%
“…Chi et al [11] studied the effects of blade tip vibrations, material properties, and spindle rotation errors on ultra-precision diamond-turned surfaces through multispectral analysis. Chen et al [12] determined the effects of the frequency response of the spindle on frequency-domain errors of machined surfaces by analyzing aerostatic spindle errors. An et al [13] examined the effects of an unbalanced aerostatic spindle on the machined surfaces of workpieces and found that the waviness errors caused by the unbalanced spindle were less than 0.1 µ m and the wavelength was approximately 100 nm.…”
Section: Introductionmentioning
confidence: 99%